Propensity to purchase organic food: its antecedents and consequences on actual purchase behavior - Khairul Nizam, Mahmud (2021)
The organic food industry is currently one of the emerging markets worldwide. People are beginning to understand the benefits of eating organic food instead of conventional food. Despite protecting the environment, people are concerned with healthy eating. This study focuses on the antecedents and consequences of actual behaviour towards the propensity to purchase organic food in Malaysia’s organic food industry. The study conceptualizes consumption value and perceived value as a multi-dimensional construct which consists of seven dimensions of values, i.e. functional value, social value, emotional value, novelty value, conditional value, monetary value, and environmental concern. Using the quantitative method, the study investigates the relationships between factors by applying the Structural Equation Modelling with Partial Least Square (SEM-PLS) version 2.0 and involves 169 respondents from Kuala Lumpur. Of the 169 respondents, 37 are male and 132 are female, with 113 Malays, 31 Chinese, 24 Indians, and 1 Other. Out of 8 hypotheses tested, only 3 are supported by the results of the study. The analyses reveal positive relationships between functional value and social value and the propensity to purchase organic food, respectively. The results also show a positive relationship between propensity to purchase and actual purchase behaviour. In this study, although the purchase of organic food in Malaysia is growing, that is 58%, the supply of local organic products is still unable to keep up with the increased demand. Therefore, the findings of this study would help practitioners, researchers and marketers, as well as organic food producers to understand which factors are important and can be applied for their future research and strategies